2005
DOI: 10.1084/jem.20042155
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of multivalent and monovalent TCRs explains high sensitivity and wide range of response

Abstract: A long-standing paradox in the study of T cell antigen recognition is that of the high specificity–low affinity T cell receptor (TCR)–major histocompatibility complex peptide (MHCp) interaction. The existence of multivalent TCRs could resolve this paradox because they can simultaneously improve the avidity observed for monovalent interactions and allow for cooperative effects. We have studied the stoichiometry of the TCR by Blue Native–polyacrylamide gel electrophoresis and found that the TCR exists as a mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
327
2
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 292 publications
(360 citation statements)
references
References 52 publications
25
327
2
6
Order By: Relevance
“…Also unknown is the role of simple monovalent ligation of individual TCRs. [212] If individual or small groups of TCRs can activate signaling, the purpose of the synapse is unclear. Multivalent ligands will undoubtedly play prominent roles in addressing these fundamental issues.…”
Section: B G-protein Coupled Receptors (Gpcrs)-gpcrsmentioning
confidence: 99%
“…Also unknown is the role of simple monovalent ligation of individual TCRs. [212] If individual or small groups of TCRs can activate signaling, the purpose of the synapse is unclear. Multivalent ligands will undoubtedly play prominent roles in addressing these fundamental issues.…”
Section: B G-protein Coupled Receptors (Gpcrs)-gpcrsmentioning
confidence: 99%
“…However, the pMHC-TCR interaction is of low affinity (4-6), making it difficult to explain how T cells achieve high sensitivity. We previously showed that the TCR was organized in nanoclusters prior to Ag engagement and that this clustering endowed T cells with higher sensitivity (7,8). Furthermore, it has long been recognized that experimental TCR ligands, such as TCR-specific Abs and soluble pMHC complexes, need to be at least bivalent to be capable of stimulating T cells (9,10).…”
Section: T He Interaction Between Cognate Peptide-mhc (Pmhc)mentioning
confidence: 99%
“…We used our previously established approach of cell surface replica generation of fixed cells labeled with primary Abs and colloidal gold-conjugated secondary reagents in combination with transmission electron microscopy (7,8). This approach permits molecular resolution of the cell surface localization of endogenous proteins and, in contrast to most high-resolution light microscopy techniques, visualizes the cell surface membrane opposite to the one in contact with the experimental support.…”
Section: Clustering Of Mhc Class I Molecules In Primary Cells and Celmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulation was done with 5 mM pervanadate; a mixture of the anti-CD3ε Ab 145-2C11 and the anti-TCRb Ab 597-H57, both at 5 mg/ml (referred to as anti-TCR in the text); 25 nM H2K d -pepABA tetramers; or 20 nM pigeon cytochrome C peptide-loaded DCEK cells (APCs) for different time points at 37˚C. Where indicated, cells were lysed in 1 ml lysis buffer containing 0.3% Brij96, as described (30). Immunoprecipitation (IP), SDS-PAGE, and Western blotting (WB) were done using standard procedures, as described (31).…”
Section: Cell Stimulation and Western Blottingmentioning
confidence: 99%